2022
DOI: 10.30541/v43i3pp.211-238
|View full text |Cite
|
Sign up to set email alerts
|

Child Health and Poverty in Pakistan

Abstract: This study examines the health status of Pakistani children using two important indicators, morbidity and malnutrition measured by weight-for-age and height-for-age. The demand for medical services has also been determined. The main data source used in this study is the 2000-01 Pakistan Social-Economic Survey (PSES), which provides sufficient information on child health and poverty. Findings of the study show that both exclusive breastfeeding during the first 4-5 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 14 publications
4
16
0
Order By: Relevance
“…Once again, this could reflect the nature of the decision-differential treatment may be more visible in participation decisions rather than more long-term health-input decisions. The absence of a gender effect in height and weight outcomes is consistent with other studies in Pakistan (Arif, 2004;World Bank, 2002 ). The signs on child age and its square imply that immunization scores increase at a decreasing rate as the child becomes older which is consistent with normal immunization behavior.…”
Section: World Developmentsupporting
confidence: 91%
See 1 more Smart Citation
“…Once again, this could reflect the nature of the decision-differential treatment may be more visible in participation decisions rather than more long-term health-input decisions. The absence of a gender effect in height and weight outcomes is consistent with other studies in Pakistan (Arif, 2004;World Bank, 2002 ). The signs on child age and its square imply that immunization scores increase at a decreasing rate as the child becomes older which is consistent with normal immunization behavior.…”
Section: World Developmentsupporting
confidence: 91%
“…Arif (2004) also notes a positive effect of mother's schooling on child height and weight outcomes using data from Pakistan from 2001 although their estimates are simple OLS estimates.…”
Section: Resultsmentioning
confidence: 97%
“…Mehmood and Mahomood (1995) concluded that boys get a preferential treatment in allocation of food relative to girls. Arif (2004) have found no gender bias for underweight and stunting of the children under five years age (Mehmood and Mahomood, 1995;Hafeez, 2001). Ali (2000) concluded that in curative or preventive health-care utilization of Pakistani children, there exists no significant difference by gender.…”
Section: Gender Of Childmentioning
confidence: 99%
“…The preventive health-care aspects are somewhat ignored. Provision of safe drinking water and underground sewage should be given priority in the social sector policies (Arif, 2004).…”
Section: Household Living Conditionmentioning
confidence: 99%
“…In this regard, planners may plan to improve the supplementary factors, that is, shift from subsistence to commercial agriculture, controlled household sizes, household dependency ratio, and initiation of non-farm employment opportunities (Datt & Jolliffe, 1999). This strategic approach may result in better income and subsequently improved access to educational, housing, and health facilities in the long run (Arif, 2000(Arif, , 2004Chaudhry, 2009;Datt & Jolliffe, 1999).…”
Section: Resultsmentioning
confidence: 99%